2022
DOI: 10.1021/acs.inorgchem.2c00242
|View full text |Cite
|
Sign up to set email alerts
|

Dysprosium(III) Metal–Organic Framework Demonstrating Ratiometric Luminescent Detection of pH, Magnetism, and Proton Conduction

Abstract: A multifunctional metal–organic framework, (Hdmbpy)­[Dy­(H2dobdc)2(H2O)]·3H2O (Dy-MOF, H4dobdc = 2,5-dihydroxyterephthalic acid, dmbpy = 4,4′-dimethyl-2,2′-bipyridine), was synthesized and structurally characterized. The metal center DyIII is connected by four carboxyl groups to form the [Dy2(CO2)4] binuclear nodes, which are further interconnected by eight separate H2dobdc2– ligands to form a three-dimensional (3D) framework including hydrophilic triangular channels and abundant hydrogen-bonding networks. Dy-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(24 citation statements)
references
References 66 publications
0
24
0
Order By: Relevance
“…Recently, several lanthanide based molecular nanomagnets have been reported for proton conduction as emerging bifunctional magnetic materials. 32–35 Herein, the supramolecular architecture showing both magnetic and electrical functions is distinct from these reported systems based on structural and synthetic viewpoints.…”
Section: Resultsmentioning
confidence: 81%
“…Recently, several lanthanide based molecular nanomagnets have been reported for proton conduction as emerging bifunctional magnetic materials. 32–35 Herein, the supramolecular architecture showing both magnetic and electrical functions is distinct from these reported systems based on structural and synthetic viewpoints.…”
Section: Resultsmentioning
confidence: 81%
“…The abnormal intracellular pH is related to many diseases, such as cancer, stroke, and Alzheimer’s disease [ 82 ]. Several fluorescent MOFs have been reported to exhibit response toward different pH values, such as PCN-225(Zn), Y(III)-MOFs and Dy-MOF [ 83 , 84 , 85 , 86 , 87 ]. Typically, Chen et al reported a dual-emission fluorescent MOF for monitoring the change of pH value with an excitation wavelength ( Figure 4 ) [ 88 ].…”
Section: Chemosensorsmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] As we know, two prominent representative applications of molecule-based magnetic materials are single molecule magnets (SMMs) and the magnetocaloric effect. [8][9][10][11][12][13][14][15][16] Warburg made the first observation of the magnetocaloric effect (MCE) in metal iron in 1881. He measured it via the change in isothermal magnetic entropy ΔS m which is based on the equation: nR ln(2S + 1)/M w .…”
Section: Introductionmentioning
confidence: 99%